Scooby-Doo! and the reluctant werewolf - Wolf, Barry; Ryan, Jim.; Paterson, Ray.; Messick, Don.; Kasem, Casey; Camp, Hamilton; Cummings, Jim.; Gerber, Joanne; Gilbert, Oscar E.; Mitchell, Brian, 1957-; Musick, Pat; Oppenheimer, Alan.; et al. (Burbank, Calif. : Warner Bros. Family Entertainment, 2002)
Count Dracula transforms Shaggy into a fuzz-faced werewolf and there's only one way he will change him back. Scooby- Doo and Shaggy must win a creepy cross-country race against a hot-rodding horde of sinister celebrity monsters.
Special features: how to draw Scooby-Doo; monster race game; DVD-ROM games; music video; trailers.
Animators, Jun Gernale, Wincat Alcala, Rico Marquez ... [et al]. ; show editor, Gil Iverson ; character designers, Mike Bennett, Eric Clark, Sue Crossley ... [et al.]
Voices: Don Messick, Casey Kasem, Hamilton Camp, Jim Cummings, Joanne Gerber, Ed Gilbert, Brian Mitchell, Pat Musick, Alan Oppenheimer.
MPAA rating: G.
Also issued on VHS.
DVD.
Keywords: Monsters -- Juvenile drama; Werewolves -- Juvenile drama; Racetracks (Automobile racing); Dracula, Count (Fictitious character); Feature films; Films for the hearing impaired; Animated films; Children's films